Implementasi KKN dalam Peningkatan Literasi Bahasa Arab melalui Kelas Interaktif di Masjid Al-Ikhlas Banaran Baru - Budiharjo, Budiharjo; ‘Amala, Aldiwa Amiku Ahsanu; Yahya, Muhammad; Fernando, Teguh; Alya, Khairunisa Nur; Fauziyah, Rima; Azahro, Rufaidah; El Muna, Alya Syahidah Asma; Febriana, Frida (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to provide guidance in introducing Arabic vocabulary to the women's study group at the Al-Ikhlas Banaran Baru Mosque, Banaran, Grogol, Sukoharjo, which is carried out by students of the Community Service Program (KKN). The activity begins with observation, material preparation, assistance in memorizing Arabic vocabulary through interactive classes, and ends with an evaluation. The method used in the interactive Arabic class is the singing method accompanied by learning to construct simple Arabic sentences. The results show that the mothers are very happy and enthusiastic in participating in this activity. It is hoped that the implementation of the interactive Arabic class will be able to increase the mothers' love for Arabic.